Reversed configuration of the muzzle imprint mark in a pistol contact entrance wound mimicking a non-suicidal act - Hejna, Petr; Šafr, Miroslav; Kramář, Roman; Kučerová, Štěpánka Pohlová; Zátopková, Lenka; Sairaj, Revathi Thirumushi; Janík, Martin (Forensic science international, 2022)
The muzzle imprint mark characteristically associated with contact or near contact entrance gunshot wounds exemplifies one of the most informative external findings in forensic medical practice. The presence of the muzzle imprint mark on the body's surface proves ballistic trauma, point of entry, and range of fire. Moreover, its appearance and configuration may indicate the type of the involved weapon and the way the firearm had been positioned and held at the time of discharge. In this paper, we present the contact shot wound pattern of an 83-year-old man who committed suicide with a Frommer Stop 12 M autoloading pistol of caliber 7.65 mm Browning. Initially, the muzzle imprint mark configuration in relation to the entrance gunshot defect in the victim's right temple indicated an unusual application or orientation of the pistol's barrel during discharge, thus, strongly suggesting a non-suicidal act. However, a critical confrontation of postmortem findings along with the results of ballistic expertise provided a clear explanation, which comprised the remarkable construction and unique muzzle design of the used handgun.
Keywords: Head Injuries, Penetrating; Suicide; Interpretation; Wounds, Gunshot; lidé; penetrující poranění hlavy; Contact shot; Aged, 80 and over; sebevražda; Entrance wound; Gunshot wound; Male; střelné rány; Forensic Ballistics; střelné zbraně; Firearms; soudní balistika; Muzzle imprint; senioři nad 80 let; mužské pohlaví; Humans